2016
DOI: 10.1021/acschemneuro.6b00122
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzylpiperidine Derivatives as α7 Nicotinic Receptor Antagonists

Abstract: Upon the study of a series of less complex derivatives, the N-benzylpiperidine motif, common to these compounds, was found to be the main pharmacophoric group. Thus, 2-(1-benzylpiperidin-4-yl)-ethylamine (48) showed an inhibitory potency comparable to the one of the previous compounds and also a clear preference for α7 nAChRs. In a neuroblastoma cell line, representative compounds 13 and 48 also inhibited, in a concentration-dependent manner, cytosolic Ca 2+ signals mediated mainly by α7 nAChRs.Finally, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The anticholinesterase ASS234 (Fig. 13), which was developed as a therapeutic for Alzheimer disease (Romero et al, 2020), was shown to be a noncompetitive antagonist of a7 and was used as a starting point to develop additional antagonists, with compound 38 proposed as a new lead compound (Criado et al, 2016). Compound 7i (Fig.…”
Section: A7 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticholinesterase ASS234 (Fig. 13), which was developed as a therapeutic for Alzheimer disease (Romero et al, 2020), was shown to be a noncompetitive antagonist of a7 and was used as a starting point to develop additional antagonists, with compound 38 proposed as a new lead compound (Criado et al, 2016). Compound 7i (Fig.…”
Section: A7 Antagonistsmentioning
confidence: 99%
“…propoxy]-1-methyl-1H-indol-2-ylgmethyl)-N-methyl-2-propyn-1-amine(Criado et al, 2016); compound 38, 2-(1-benzylpiperidin-4-yl)ethan-1-amine(Criado et al, 2016); compound 7i, N-((1-benzylpiperidin-4-yl)methyl)-1-(2chlorobenzyl)-N-methyl-1H-1,2,3-triazole-4-carboxamide (Peng et al, 2010); B10, 3-(4-bromophenyl)-8-methyl-1-oxa-2,4,8-triazaspiro[4.5]dec-2-ene (Zhang et al, 2020a); mecamylamine, N,2,3,3-tetramethylbicyclo[2.2.1]heptan-2-amine;hydrochloride; tkP3BzPB, 1,2,4,5-tetra-f5-[1-(3-benzyl)pyridinium]pent-1-ylgbenzene tetrabromide; and MLA. Therapeutic Targeting of a7 nAChR…”
mentioning
confidence: 99%
“…Its antagonists (e.g., d ‐tubocurarine or snake's neurotoxin) exert an inhibitory effect on tumors. However, the reagents used in rats cannot be used in clinical settings because of their high toxicity 12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…However, the reagents used in rats cannot be used in clinical settings because of their high toxicity. [12][13][14][15] Meanwhile, 7 nAChR, as a crucial receptor of neuroimmune networks, is observed in multiple immunocytes, such as M s and lymphocytes. The cholinergic anti-inflammatory pathway (CAP) is among the manifestations in neuroimmune networks.…”
mentioning
confidence: 99%